An ideological analysis of the construction of the young female action hero as feminist hero in The Hunger Games film franchise - Mathurine, Kim Elizabeth (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
Young female action heroes have recently stepped into the limelight as commercial celebrations of Girl Power in Hollywood action-adventure films. Feminist films studies however have shown that these independent, tough female heroes claimed as feminist, are still constrained in various ways through stereotypical gender roles within the action-adventure genre. This thesis examines these claims through the ideological analysis of the young female action hero Katniss in The Hunger Games film franchise. Building on existing research on female action heroes, the research asks: 'to what degree can the claim of Katniss as boundary-breaking, feminist hero be validated'? This question is addressed through a textual analysis of the four films of The Hunger Games film franchise, employing conventions of action-adventure genre, narrative analysis, mise-en-scène and cinematography to unmask the characterisation of the female hero. The discussion of the findings, utilising the themes of Love, Violence and Power, reveal both progressive and regressive elements present in the characterisation of Katniss. The findings indicate that while female action heroes can be celebrated for displaying progressive moments of liberated action, they remain constrained within dominant heteronormative gender roles in commercial Hollywood films, undergoing various acts of transformation and recuperation as a means of containing the threat of their transgressive behaviour.
Keywords: Everdeen, Katniss (Fictitious character); Women superheroes in motion pictures; Hunger Games films; Feminist film criticism; Feminism and motion pictures; Women in motion pictures